Single dose treatment of vaginal candidosis: comparison of clotrimazole and isoconazole. Issue 1 (February 1984) - Cohen, L
Abstract : The therapeutic efficacy of a single dose 500 mg tablet of clotrimazole was compared with two 300 mg tablets of isoconazole in an open randomised study of 100 patients with vaginal candidosis confirmed by mycological culture. One week after treatment 100% of the clotrimazole treated patients and 98% of the isoconazole treated group gave mycologically negative results. Five weeks after treatment these figures were 74% and 78% respectively, showing that both regimens were equally effective.